Extracorporeal Membrane Oxygenation in an Adolescent with Multisystem Inflammatory Syndrome in Children - Gago, Cristina; Lorenzo, Cristina; Pinto, Sara; R. Sousa, Ana; Camilo, Cristina; Abecasis, Francisco (Acta Médica Portuguesa, 2023)
Multisystem inflammatory syndrome in children is a rare and potentially life-threatening disease that is associated with SARS-CoV-2 infection, characterized by hyperinflammation and multiorgan involvement. Cardiovascular involvement is common, including myocardial dysfunction often leading to cardiogenic shock. We present the case of a 17-year-old boy with fever, odynophagia, maculopapular rash and abdominal pain who developed a cardiogenic shock. Due to progressive deterioration of cardiac function despite optimized vasoactive support, veno-arterial extracorporeal membrane oxygenation support was initiated 12 hours after admission, with successful decannulation after seven days and discharge after 23 days, with normal cardiac function. The patient received corticosteroids and intravenous immunoglobulin. Early recognition and intensive care support are crucial for ensuring a successful outcome in severe cases of multisystem inflammatory syndrome. In cases of severe cardiogenic shock, extracorporeal membrane oxygenation support can be critical for survival and rapid recovery.